Application of Demonstration and Experiment Methods in Fiqh Learning in Improving Student Psychomotor Skills - Nurazizah; Zainuddin, Ammar; Ismawati (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The purpose of this thesis is to obtain object data in the field about the application of demonstration methods and experiments in fiqh learning in improving the psychomotor of MIN 11 Banda Aceh students, Aceh Province. The problem raised by the researcher is how to apply demonstration and experimental methods to fiqh lessons in MIN 11 Banda Aceh, Aceh Province and how to improve the psychomotor skills of students of MIN 11 Banda Aceh, Aceh Province? The research method used in the research is a qualitative research method that is descriptive by using observation, interview, documentation, and questionnaire methods as supporting existing data. The results of the research obtained are to provide an overview that the application of demonstration and experiment methods in MIN 11 Banda Aceh, Aceh Province has been going well and however, there are several obstacles faced by fiqh teachers in MIN 11 Banda Aceh, especially the limitations of demonstration tools and adjusting to the material. Meanwhile, regarding the improvement of students' psychomotor skills, it can be found when the teacher demonstrates a material where the students seem to be more active both in listening and when responding to the teacher's invitation or question. The application of the demonstration method is more dominant used by teachers than the experimental method, this is due to the limitations of teaching aids and also the time that is not possible to experiment to all students, in the application of the demonstration method there are also teachers who use audio visuals as a tool to make it easier and faster for students to understand.